100 Years of Prandtl's Wedge - Stefan Van Baars (IOS Press, 2018)
The biggest problem for a shallow foundation, just as for any other type of foundation, is a failure due to an overestimation of the bearing capacity. This means that the correct prediction of the bearing capacity of the foundation is often the most important part of the design of a civil structure. That is why the publication by Prandtl in 1920 about the hardness of a plastic body, was a major step in solving the bearing capacity of shallow foundations, although it is well possible that he never realised this, because his solution was not made for civil engineering purposes, but for mechanical purposes. Over the last 100 years, a lot of extensions have been made, for example with inclination factors and shape factors. Also many laboratory experiments have been done and numerical calculations have been made. Some even try to extrapolate the failure mechanism for shallow foundations to the failure mechanism around the tip of a pile. All this scientific work leads back to the first publication by Ludwig Prandtl in 1920. This book, "100 Years of Prandtl's Wedge", is intended for all those who are interested in these fundamentals of foundation engineering and their history. The Appendices include a copy of Prandtl's Über die Härte plastischer Körper and of Reissner's publication of 1924, Zum Erddruckproblem.